2002
DOI: 10.1002/cncr.10838
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low‐dose topotecan in second‐line treatment for patients with epithelial ovarian carcinoma

Abstract: Topotecan at a dose of 1.0 mg/m(2) has similar efficacy based on response rate and lower toxicity compared with the approved schedule of 1.5 mg/m(2) for 5 days every 3 weeks in second-line treatment for patients with platinum-resistant and paclitaxel-resistant epithelial ovarian carcinoma. However, a comparison of different topotecan doses and schedules preferably should be made in a randomized setting in well-characterized populations with regard to established prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 30 publications
(32 reference statements)
1
13
0
Order By: Relevance
“…Prospective studies have evaluated the potential role of lower-dose topotecan (1.0-1.25 mg/m 2 daily on days 1-5 of a 21-day course) in patients with heavily pretreated platinum-and paclitaxel-resistant or refractory ovarian cancer [18,[49][50][51][52]. The individual response rates for those studies are summarized in Table 4 [18, [49][50][51][52].…”
Section: Dose Reductionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective studies have evaluated the potential role of lower-dose topotecan (1.0-1.25 mg/m 2 daily on days 1-5 of a 21-day course) in patients with heavily pretreated platinum-and paclitaxel-resistant or refractory ovarian cancer [18,[49][50][51][52]. The individual response rates for those studies are summarized in Table 4 [18, [49][50][51][52].…”
Section: Dose Reductionsmentioning
confidence: 99%
“…The individual response rates for those studies are summarized in Table 4 [18, [49][50][51][52]. Among the 151 evaluable patients in five studies with platinum/paclitaxelresistant patients, 7%-22% achieved a response lasting from 3-10 months; stable disease (SD) was observed in 18%-60% of evaluable patients.…”
Section: Dose Reductionsmentioning
confidence: 99%
“…A similar conclusion has been suggested by several authors regarding the importance of modifying the dose of liposomal doxorubicin that is delivered in platinum-resistant ovarian cancer [5][6][7] , as well as the use of topotecan for this identical clinical indication [8][9][10] .…”
mentioning
confidence: 59%
“…Alternative schedules may provide higher tumor response rates and less myelosuppression compared to standard dose schedule. Several alternative dosing schedules like 21-day 24-hour continuous IV, a 3-day IV bolus, a weekly 72-hour continuous IV, and a weekly IV bolus regimen were explored in phase I and phase II clinical trials [26][27][28][29][30][31] . Although all of these trials have shown varied results, they can still be considered as promising.…”
Section: Discussionmentioning
confidence: 99%